The use of motivational interviews by nurses to promote health behaviors in adolescents: a scoping review protoco - Lomba, Maria de Lurdes Lopes de Freitas (2016)
The objective of this scoping review is to examine and map the use of motivational interviews (MI) by nurses in their clinical practice with adolescents to promote health behaviors.More specifically, the review will focus on the following questions:What is the current nature and extent of use of nurse-led MI in the promotion of health behaviors in adolescents?Which adolescent populations (in terms of health status and adoption or not of health risk behaviors have been included in nurse-led MI with the aim of promoting health behaviors?What are the contexts in which nurses have used MI to promote health behaviors in adolescents?Which specific MI techniques and/or strategies have been used by nurses to promote health behaviors in adolescents?What outcomes on the promotion of health behaviors have been reported from nurse-led MI with adolescents?